Content Analysis of Animation Video Instagram Account @Marhaban.Academy as a Medium for Learning Arabic Vocabulary - Sari, Lubna (Institut Agama Islam Negeri Palangka Raya, 2023)
The challenge for Arabic language teachers in the digitalization era is how creative they can be in using technology, especially in learning Arabic, which is still often considered a complex subject. Based on the results of researchers' observations, Instagram as a technology product has many accounts that discuss Arabic learning material, such as the Instagram account @marhaban.academy. The Instagram account @marhaban.academy contains content discussing Arabic vocabulary. Therefore, this research aims to discover the features of video content and whether learning videos on Instagram accounts can be used as a medium for learning Arabic. A descriptive qualitative approach with a type of content analysis with a descriptive qualitative approach was used in this research. The results of this research show three features used in Arabic vocabulary learning video content on the Instagram account @marhaban.academy, such as animated videos, sound, and writing. The interview results show that these three features help students to know and increase their Arabic vocabulary. From the results of this research, researchers recommend using Arabic social media content to support Arabic language learning outcomes.